Separation of Complex Esters from Cuminum by Chromatographic Analysis Method (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
The chemical composition of the ethanol extract of cuminum seeds was studied using chromato-mass spectrometry. 30 compounds were identified, for which mass spectra and structural formulas were obtained, the quantitative content of the latter was determined, and the structural group composition of the extract was calculated. The basis of the extract is alcohols with the dominance of dihydric, ketones, aldehydes, esters and ethers